THE CONTIGUITY OF MUSA’S SHARIA IN THE QURAN: TORAH AND ṢUḤUF TERMINOLOGY IN EXEGETICAL LITERATURES - Saputra, Ali Thaufan Dwi; Ansari, Miftach (Peminat Ilmu Ushuluddin, 2023)
This article attempts to trace the contiguity of the substance of the sharia revealed to Musa in the Quran by tracing the terminology of the Torah and Ṣuḥuf on exegetical sources. The article will track the intersection of the classical and contemporary exegetical sources that use the jurisprudence approach as a lens in interpreting the Quran. This research is qualitative in nature, and the method used is descriptive-analytical. As a result, at least based on exegetical literature, there is a specific intersection between the sharia brought by Musa and the sharia brought by Muhammad in the Quran. The intersection lies, for example, in legal aspects such as qiṣāṣ, diyāt and rajam. However, there are different views on addressing this contiguity. One view is that the contiguity does not mean anything because the previous sharia has been abolished by the revelation of the Quran. Another view states that the Quran is a conclusive-confirmative revelation and does not abolish previous sharia.